Late‐Stage Functionalization of Histidine in Unprotected Peptides. Issue 52 (7th November 2019) - Noisier, Anaïs F. M.; Johansson, Magnus J.; Knerr, Laurent; Hayes, Martin A.; Drury, William J.; Valeur, Eric; Malins, Lara R.; Gopalakrishnan, Ranganath
Abstract: The late‐stage functionalization (LSF) of peptides represents a valuable strategy for the design of potent peptide pharmaceuticals by enabling rapid exploration of chemical diversity and offering novel opportunities for peptide conjugation. While the C(sp 2 )−H activation of tryptophan (Trp) is well documented, the resurgence of radical chemistry is opening new avenues for the C−H functionalization of other aromatic side‐chains. Herein, we report the first example of LSF at C2 of histidine (His) utilizing a broad scope of aliphatic sulfinate salts as radical precursors. In this work, the exquisite selectivity for histidine functionalization was demonstrated through the alkylation of complex unprotected peptides in aqueous media. Finally, this methodology was extended for the installation of a ketone handle, providing an unprecedented anchor for selective oxime/hydrazone conjugation at histidine. Abstract : C−H(is) functionalization : The first example of chemoselective C‐2 alkylation of histidine‐containing peptides through a mild Minisci‐type reaction is described. This new approach enables the rapid exploration of chemical diversity around this underexplored residue and provides a novel opportunity for the labelling and conjugation of peptides.